Review of the subgenus Geron (Geron) Meigen in the Nearctic Region (Diptera: Bombyliidae: Toxophorinae) - Hall, Jack C.; Evenhuis, Neal L. (Zootaxa, 2003)
The bombyliid subgenus Geron (Geron) Meigen as it occurs in the Nearctic Region is reviewed. A total of 28 species are found to comprise the subgenus in the Nearctic. The following 16 new species are described and illustrated: Geron albipilosus Hall & Evenhuis, sp. nov., G. borealis Hall & Evenhuis, sp. nov., G. confusus Hall & Evenhuis, sp. nov., G. cressoni Hall & Evenhuis, sp. nov., G. elachys Hall & Evenhuis, sp. nov., G. eriogonae Hall & Evenhuis, sp. nov., G. halli Evenhuis, sp. nov., G. infrequens Hall & Evenhuis, sp. nov., G. monticola Hall & Evenhuis, sp. nov., G. nevadensis Hall & Evenhuis, sp. nov., G. notios Hall & Evenhuis, sp. nov., G. painteri Hall & Evenhuis, sp. nov., G. peucon Hall & Evenhuis, sp. nov., G. prosopidis Hall & Evenhuis, sp. nov., G. stenos Hall & Evenhuis, sp. nov., and G. weemsi Hall & Evenhuis, sp. nov. The following are found to be new junior synonyms: Geron perplexus Tabet, 2001 = Geron argutus Painter, syn. nov., G. saxosus Tabet, 2001 = G. holosericeus Walker, syn. nov., and G. antologos Tabet, 2001 = G. senilis (Fabricius, 1794), syn. nov.